Consider this function in explicit form.

f(n)=3n-4; n>1

Select the equivalent recursively defined function.

A. f(1)= -1; f(n)=f(n-1)+3; n>2

B. f(1)= -1; f(n)=3f(n-1)+3; n>2

C. f(0)= -4; f(n)=3f(n-1)+3; n>2

D. f(0)= -4; f(n)=f(n-1)+3; n>2
asked Nov 8, 2016 in Algebra 1 Answers by marieh_ (220 points)

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

f(n)=3n-4 so f(0)=-4, f(1)=-1, f(2)=2, f(3)=5. (f(4)=8, etc., so it's clear that f(n)=f(n-1)+3.)

In C, D f(0)=-4 and in A, B f(1)=-1. So they are consistent.

In A, f(2)=f(1)+3=-1+3=2 the same as f(2) originally and f(3)=f(2)+3=2+3=5 the same as f(3) originally.

The other options (B and C) are not consistent with the original f(n). So the answer is A. D appears to be the same as A because f(0)=-4 and f(1)=-1 for both A and D.

answered Nov 8, 2016 by Rod Top Rated User (429,740 points)
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
78,077 questions
81,873 answers
1,828 comments
61,268 users